1997
DOI: 10.1016/s0735-1097(96)00575-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Myocardial Perfusion in Multiple Echocardiographic Windows With One Intravenous Injection of Microbubbles Using Transient Response Second Harmonic Imaging

Abstract: Transient response imaging produces myocardial contrast in multiple views with one intravenous injection of contrast agent and can accurately identify regional myocardial perfusion abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(47 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…The fact that microbubbles respond differently to the ultrasound depending upon the degree of insonating acoustic power (mechanical index) has led to the development of harmonic and intermittent triggered imaging technologies [4][5][6]. On top of these two technologies, there have been a number of refinements and modifications of imaging technologies to enhance nonlinear signals from the microbubbles and simultaneously reduce the linear signals from the tissue as much as possible.…”
Section: Technologies To Enhance Nonlinear Signals From Microbubbles mentioning
confidence: 99%
“…The fact that microbubbles respond differently to the ultrasound depending upon the degree of insonating acoustic power (mechanical index) has led to the development of harmonic and intermittent triggered imaging technologies [4][5][6]. On top of these two technologies, there have been a number of refinements and modifications of imaging technologies to enhance nonlinear signals from the microbubbles and simultaneously reduce the linear signals from the tissue as much as possible.…”
Section: Technologies To Enhance Nonlinear Signals From Microbubbles mentioning
confidence: 99%
“…Of these 3 methods, only scintigraphy directly assesses perfusion. Myocardial contrast echocardiography is an alternative method for scintigraphy because it provides reproducibility, real-time image assessment, in addition to being noninvasive and relatively inexpensive 1 . All comparative studies between both methods have shown an acceptable concordance, validating the use of contrast echocardiography as an alternative for myocardial nuclear scintigraphy [2][3][4][5] .…”
Section: Abstract Echocardiography Myocardial Perfusion Echocardiomentioning
confidence: 99%
“…Newer myocardial contrast techniques are being developed, however, that permit the simultaneous analysis of wall motion and perfusion with contrast echocardiography. These involve using a lower mechanical index, which permits the use of a higher frame rate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). At this frame rate, both wall motion and perfusion can be analyzed simultaneously.…”
Section: Study Limitationsmentioning
confidence: 99%
“…New perfluorocarbon containing ultrasound contrast agents consistently opacify the myocardium following venous injection or infusion, with more consistent and reliable results, compared with first-generation ultrasound contrast agents containing room air as gases in microbubbles. 8 Also, new ultrasound imaging techniques [10][11][12] that reduce microbubble destruction (e.g., intermittent harmonic imaging) have detected myocardial perfusion abnormalities both during dipyridamole [13][14][15][16] and dobutamine 17 stress. These preliminary studies have been relatively small in size, and at single sites.…”
Section: Introductionmentioning
confidence: 99%